How to carry out a Brazilian research in computing considering ethical or moral aspects? - Carvalho, Luiz Paulo; Costa, Rosa Maria M. Da; Santoro, Flávia Maria; Oliveira, Jonice (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: Ethical aspects are of increasing interest to the computing communities. Part of this interest is related to ethics in research and institutional ethics related to research ethics committees. This phenomenon has also increased ethical or moral demands by institutions and academic-scientific collectives. Problem: Research in Ehics presents several issues, challenges, and difficulties, which go beyond a basic or superficial knowledge. These deficiencies or limitations have negative ethical consequences, including in a political sense, for the Brazilian computing community. Solution: We bring a collection of objective and informative reflections on these topics, which are rarely addressed or found in the computing literature, adequately suited to the IS context. Theory: Qualitative approach through Hermeneutics, Critical social theory, and Theory of reasoned action. Research method: Prescriptive and transformative, based on ethnography and autoethnography methodologies. Results and contributions to IS: We present several abstract and concrete considerations about advanced or non-trivial research ethics and ethics committee topics. We call the Brazilian computing community for advances in the agency of ethical or moral aspects, for moral advancement and sociotechnical awareness. The contribution addresses several issues, challenges, and difficult to find or unprecedented interpretation, e.g., involving data from social networks, annotators, children, internationalization, i.a. Aiming to promote moral maturity, as a common and shared understanding.